2008
DOI: 10.1088/0022-3727/42/1/015204
|View full text |Cite
|
Sign up to set email alerts
|

Line-type inductively coupled plasma source with ferromagnetic module

Abstract: The characteristics of a line-type, internal antenna for an inductively coupled plasma (ICP) source installed with a ferromagnetic module were investigated for possible application to roll-to-roll processing of next-generation display devices. The use of 2 MHz instead of 13.56 MHz for the 2300 mm long ICP source improved the plasma uniformity to less than 11% along the antenna line. In addition, the use of Ni-Zn ferromagnetic material in the line-type antenna improved the plasma density to about 3.1 × 10 11 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The increase in the magnetic field caused by the ferrite module is related to the concentration of the induced magnetic field in the area between the antenna and the substrate. From the Ampere's law of H c B Á ds ¼ l ferrite l 0 I (where, s is the area measured around antenna center, l 0 : magnetic constant of free space, l 0 ¼ 4p  10 À7 Hm À1 , l ferrite : the permeability of the ferrite * 500), it can be shown that the time-varying B field measured below the antenna line is represented by the equation B ¼ l 0 I=2pr (where, r is the radius from the antenna center) when the ferrite module is not used [13]. However, by installing the ferrite module, which covers the top half of the antenna line, the magnetic field induced in the area between the antenna and the chamber wall can be diverted by the ferrite to the area between the antenna and the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the magnetic field caused by the ferrite module is related to the concentration of the induced magnetic field in the area between the antenna and the substrate. From the Ampere's law of H c B Á ds ¼ l ferrite l 0 I (where, s is the area measured around antenna center, l 0 : magnetic constant of free space, l 0 ¼ 4p  10 À7 Hm À1 , l ferrite : the permeability of the ferrite * 500), it can be shown that the time-varying B field measured below the antenna line is represented by the equation B ¼ l 0 I=2pr (where, r is the radius from the antenna center) when the ferrite module is not used [13]. However, by installing the ferrite module, which covers the top half of the antenna line, the magnetic field induced in the area between the antenna and the chamber wall can be diverted by the ferrite to the area between the antenna and the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…This holds for not too many turns, when rf current caused by the coil stray capacitance is negligible compared with the coupler current I 1 . Similar considerations are fully applicable to couplers enhanced with ferromagnetic cores [9,12,34,54,55] described in section 4.1. The fundamental limitation of these types of FMICP (shown in figure 27) is caused by their structure which consists of a thin antenna conductor partly surrounded by a ferromagnetic shield core.…”
Section: What Makes Efficient Icp Sourcementioning
confidence: 88%
“…Another scheme of FMICP for large area processing has been proposed and studied in [54,55] used in those works is shown in figure 23. An immersed (internal) U-shaped antenna is covered with a quartz tube, then with a half-tube (inversed gutter) ferrite shield, and the entire structure is encapsulated in another quartz tube to protect the ferrite shield from chemical interaction with plasma.…”
Section: Fmicps With Open Ferrite Corementioning
confidence: 99%
See 2 more Smart Citations